2019
DOI: 10.3390/biom9010030
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Bioactivities of Tobacco Cembranoid Diterpenes

Abstract: Cembranoids are carbocyclic diterpenes comprising four isoprene units and are natural products with a parent skeleton consisting of a 14-membered ring. They have gained wide interest in recent years and are a major hotspot in the research of natural product chemistry. Since 1962, various tobacco cembranoid diterpenes have been identified. This review systematically discusses and summarises the excellent antimicrobial, insecticidal, cytotoxic and neuroprotective activities of tobacco cembranoid diterpenes. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…activity was produced by 4R at a concentration of 397μM, considerably higher than the EC50 at 0.8μM at which 4R induces neuroprotection in ex vivo hippocampal slices [24,25]. In the present work, treatment with LPS and 4R at 1.53μg/mL (5μM) differentially regulated close to 400 genes related to canonical pathways from the cell cycle to inflammation.…”
Section: Discussionmentioning
confidence: 56%
“…activity was produced by 4R at a concentration of 397μM, considerably higher than the EC50 at 0.8μM at which 4R induces neuroprotection in ex vivo hippocampal slices [24,25]. In the present work, treatment with LPS and 4R at 1.53μg/mL (5μM) differentially regulated close to 400 genes related to canonical pathways from the cell cycle to inflammation.…”
Section: Discussionmentioning
confidence: 56%
“…Incidents of other infections, such as in luenza virus in Yemen is less than those in neighbor countries [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Tobaccomentioning
confidence: 99%
“…The previous chemical investigations of N. tabacum indicated that 46 isolated compounds could be divided into nine categories: diterpenoids (1-6), sesquiterpenes (7-13), furan-2-carboxylic acids (14)(15)(16)(17)(18)(19)(20)(21)(22), flavonoids (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), sterols (33-36), 2-arylbenzofurans (37,38), isobenzofurans (39-41), phenylpropanoids (42)(43)(44)(45), and aminoglucoside (46). Among them, terpenes and flavonoids were predominant (Figure 1).…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…Cembranoid is one of the characteristic chemical constituent of N. tabacum featured with four isoprene units in the parent skeleton of a 14-membered ring. [29] These ingredients are present in not only the plants belonging to the genera Nicotiana and Pinus, but also marine organisms (e.g., soft coral). [30] In the continuous searches for active compounds from N. tabacum,…”
Section: Chemical Constituentsmentioning
confidence: 99%